Pengaruh Perceived Ease of Use dan Perceived Usefulness terhadap Loyalitas dengan Trust sebagai Variabel Intervening terhadap Penggunaan Aplikasi Warung Pintar - Nur Faizah; Sanaji Sanaji (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aims to determine the effect of perceived ease of use and perceived usefulness on loyalty with trust as an intervening variable. This study uses a quantitative approach. The sampling technique is a non-probability technique with the type of judgmental sampling. Data collection was done by distributing questionnaires. The number of respondents obtained as many as 245 people. The research method used is path analysis. The results obtained in this study are that perceived ease of use has a positive and significant effect on perceived usefulness. Perceived ease of use has a positive and significant effect on trust. Perceived usefulness has a positive effect on trust. Trust has a positive and significant effect on loyalty. Perceived ease of use has no effect on loyalty. And perceived usefulness has a positive and significant effect on loyalty. PT. Warung Pintar Distribusi is expected to pay more attention to reviews from partners regarding the use of aplikasi warung pintar and optimize the features in aplikasi warung pintar.